THE ROLE OF STRATEGIC MANAGEMENT OF LEADERS IN MANAGING ISLAMIC EDUCATIONAL INSTITUTIONS - Dantika, Fina Azizah; Nugraha, Mulyawan Safwandy (STIT PRINGSEWU, 2024)
Abstract: An ideal leader is someone whose life and personality can inspire others to emulate. A good leader is authoritative, has a righteous way of life, and is worthy of being a role model. This is not due to their power, prestige, personality, or specific status. On the other hand, most